THE STRUGGLE OF THE ACEH DAYAH ULAMA ASSOCIATION (HUDA) IN PRESERVING THE DOCTRINE OF AHLUSUNNAH WALJAMAAH IN ACEH - Syafieh, Syafieh; Nur, Afrizal (State Islamic University North Sumatra, 2022)
Abstract: This study discusses the Aceh Dayah Ulama Association (HUDA), which traditionalist Islamic groups use as an organization that maintains the dominant Islamic ideology by using the dayah network as the basis of the religious movement. By using the theory of religious movement, through participatory observations, in-depth interviews with HUDA administrators and the Acehnese people as well as a study of the literature, this paper ultimately demonstrates the ability of the dayah ulama to use HUDA as networking among the dayah scholars as evidence of a scientific genealogy among the Dayah scholars in Aceh. In addition, HUDA is used by dayah ulama to strengthen the hegemony of traditionalist Islam as a group that has religious authority amid the rise of Wahhabi-Salafi schools in Aceh and as political bargaining with the government to determine the direction of government policy in religious matters. This article only discusses the dayah ulama members of HUDA and their strategies in defending the Ahlusunnah waljamâ‘ah doctrine. Keywords: Ulama, Religious Social Movement, Aswaja, Aceh, Indonesia